Disparities in use of mental health and substance abuse services by Asian and Native Hawaiian/Other Pacific Islander women - Duggan, A. (2008)
The purpose of this study was to determine if disparities exist in lifetime utilization of mental health/substance abuse services among Asian, Native Hawaiian/Other Pacific Islander (NHOPI) and white mothers. The study sample was comprised of mothers assessed to be at-risk (n = 491) and not at-risk (n = 218) for child maltreatment in the Hawaii Healthy Start Program study. Multiple logistic regression models were used to test the effects of predisposing, need, and enabling factors on utilization of services. Results revealed that, among mothers with depressive symptoms, compared with whites, Asians and NHOPI were significantly less likely to have received services. There were no significant racial differences in use of mental health/substance use services by other factors. These results suggest that racial disparities exist in utilization of mental health/substance abuse services among mothers with depressive symptoms. Future research is needed to identify barriers and facilitators to accessing needed services for Asian and NHOPI women